Gambaran Kesiapan Menghadapi Menarche Pada Siswi Kelas V SD Swasta Katolik Assisi Medan Tahun 2024 - Yunika Simanjuntak; Friska Sri Handayani Ginting; Murni Sari Dewi Simanullang (STIKES Columbia Asia Medan, 2025)
Menarche marks the onset of a young woman's first menstruation and requires both physical and psychological adjustments to achieve personal maturity. Therefore, adequate preparation is essential for adolescents as they experience this transition. Readiness for menarche involves various adaptations, including physical, psychological, and social aspects. This study aims to explore the level of menarche readiness among fifth-grade female students at Assisi Catholic Private Elementary School, Medan, in 2024. The research employs a descriptive method with a cross-sectional approach, utilizing the Accidental Sampling technique with a total of 34 respondents. Data collection was conducted using a questionnaire assessing menarche readiness, and the analysis was performed using univariate methods. The findings reveal that out of 34 respondents, the majority (30 students or 88.2%) were prepared for menarche, while only 4 students (11.8%) were not yet ready. This study is expected to serve as a valuable resource for schools in providing menarche education, thereby enhancing students' readiness for this important stage of development.